Molecular Breeding in Wheat, Maize and Sorghum: Strategies for Improving Abiotic Stress Tolerance and Yield 2021
DOI: 10.1079/9781789245431.0019
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular interventions for improving nitrogen-use efficiency in maize.

Abstract: This chapter discusses (i) the importance of nitrogen in plant growth and development, (ii) what is nitrogen-use efficiency (NUE) and how to manage it, (iii) traits influencing nitrogen-uptake efficiency including root system architecture, root nitrogen transporter system, and interaction with microorganisms, (iv) traits influencing nitrogen-utilization efficiency, such as nitrate assimilation, canopy photosynthesis per unit of nitrogen, (v) identification and use of quantitative trait loci (QTLs) related to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Different types of slow-release fertilizers (SRF) have been developed to improve NUE and reduce potential environmental losses (Giday, 2019;Giday et al, 2014). For example, controlled-release fertilizers (CRF) and nitrification inhibitors (NI) can either slow down nutrientrelease patterns and/or interfere with nutrient transformation processes and reduce their loss (Singh et al, 2018). It potentially delays the N release pattern and reduces N losses, which may improve the synchronization potential between crop demand and soil N supply (Giday et al, 2014).…”
Section: Soil Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of slow-release fertilizers (SRF) have been developed to improve NUE and reduce potential environmental losses (Giday, 2019;Giday et al, 2014). For example, controlled-release fertilizers (CRF) and nitrification inhibitors (NI) can either slow down nutrientrelease patterns and/or interfere with nutrient transformation processes and reduce their loss (Singh et al, 2018). It potentially delays the N release pattern and reduces N losses, which may improve the synchronization potential between crop demand and soil N supply (Giday et al, 2014).…”
Section: Soil Managementmentioning
confidence: 99%
“…Tamene et al (2016) demonstrated that poor weed management increases competition for soil nutrients, moisture, and sunlight, which affects resource use efficiency and crop productivity. Therefore, maintaining these factors at the threshold level is important for enhancing yield and NUE (Singh et al, 2018).…”
Section: Crop Rotation and Using Biological N-fixing Cropsmentioning
confidence: 99%
“…By continuously monitoring and analyzing data related to soil health, crop requirements, and nutrient content, these systems provide real-time insights into the nutritional needs of plants. This granular approach ensures that crops receive the appropriate nutrients at the right time and in the right quantities, promoting optimal growth and minimizing waste (Singh, et al, 2018). The implementation of AI in resource management contributes to a more environmentally sustainable agriculture sector (Mouchou et al, 2021, Owebor et al, 2022.…”
Section: Resource Management Through Aimentioning
confidence: 99%
“…Autumn film mulched ridge microfurrow rainwater harvesting (ARF) planting, which is a combination of film mulching and ridge-furrow rainwater harvesting tillage, has been widely adopted for potato production in Northwest China [28,29]. ARF integrates the use of high-yielding and nutrient-efficient varieties [10,19,[30][31][32][33], 4R (right source, right rate, right time, and right place) best practices for fertilization management [34,35], the effective regulation of soil water fertility conditions [36], and major benefits for improving the NUE F [18,[36][37][38]. Studies have shown that ARF produces the highest tuber yield and good potato quality, mainly because of the significantly increased potato water-use efficiency [11,39,40]; however, whether it increases the NUE F is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…N is the primary component of chlorophyll, nucleic acids, proteins, amino acids, coenzymes, and membrane constituents [46]. Increasing the N-use efficiency can increase vegetative growth [35] and the proportion of large tubers [10,17,47,48]. P is involved in energy transfer, photosynthesis and respiration, rapid canopy development, root cell division, tuber set, and starch synthesis [17,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%